Pengaruh Motivasi Kerja, Loyalitas dan Kualitas Karyawan Terhadap Kinerja Karyawan di PT. Indofood CBP Sukses Makmur Tbk - Rumampuk, Tasya Laudita; Mandamdari, Alpha Nadeira; Nurdiani, Ulfah (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Human resources have a very important role in supporting the sustainability of a company or organization. The purpose of this study was to analyze the effect of work motivation, loyalty and quality of employees on employee performance at PT. Indofood CBP Sukses Makmur Tbk, Noodle Division, Bekasi West Java Branch. Respondents in this study were 130 employees from a total population of 2620 employees who were divided into permanent employees and contract employees, spread several departments with a sampling technique using stratified random sampling. The data analysis used in this study includes descriptive analysis of respondents, multiple linear regression analysis and multivariate ANOVA test. The results showed that: 1) work motivation had a significant effect on employee performance. 2) Loyalty had a significant effect on employee performance. 3) Employee quality had a significant effect on employee performance. 4) Work motivation, loyalty and quality of employees together significant affect employee performance. 5) Contract employees have better work motivation, 6) permanent employees have loyalty, employee quality and better performance, it can be seen from how permanent employees are better able to analyze, assess, create and make decisions on problem-solving and are able to find solutions to a problem that is around. Keywords: employee performance, employee quality, loyalty, work motivation